PEMANFAATAN PATI KULIT SINGKONG SEBAGAI EDIBLE COATING PADA BUAH JAMBU AIR - Diyah Suriani; Fajar Restuhadi; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study is aimed to obtain the shelf-life preservation of watery rose apple coated by an edible coating from cassava-peel starch. This research method used an experimental method using a completely randomized design (CRD) consisting of four treatments and four replications in order to obtain 16 experimental units. The treatments in this study were P0 = storage of watery rose apple for 0 days, P1 = storage of watery rose apple for 5 days, P2 = storage of watery rose apple for 10 days, and P3 = storage of watery rose apple for 15 days. The parameters observed in the edible coating were weight loss, vitamin C content, descriptive sensory tests, color and physical hardness. Data were analyzed statistically using variance (ANOVA) and followed by Duncan’s New Multiple Range Test(DNMRT) at level 5% level. The selected treatment chosen was watery rose apple in treatment P2 with a weight loss of 3,46%, and vitamin C content of 1,00 mg/100 g,while descriptively have a score of 3,63 (red), hardness with a score of 2.97 (slightly hard). Based on the regression analysis, physical hardness of watery rose apple could be maintained for up to 8,11 days of storage. Keywords: Watery rose apple, cassava peel starch, edible coating, shelf-life